Tingkat Kesehatan Bank BUMN dan Bank Swasta yang Terdaftar di Bursa Efek Indonesia - Kosim, Belliwati; Pratama, Reggi Agustian (Universitas muhammadiyah palembang, 2021)
This study aimed to find out the differences in soundness level of state-owned banks and private banks listed on the Indonesia Stock Exchange. This research was included in the type of descriptive quantitative research with research subjects of state-owned banks and private banks listed on the Indonesia Stock Exchange for the period 2015-2019. In this study, there were 8 research samples with the purposive sampling method. Data collection techniques used documentation and data analysis techniques in financial analysis and statistical analysis used Anova-one way test. The results of this study indicated that the RGEC value did not have differences between state-owned banks and private banks, then in the RGEC indicator test it stated that there were no differences between state-owned banks and private banks, this was because the soundness level of the bank was a major factor in the supervision of the financial services authority (OJK) based on Indonesia bank regulations.